2021
DOI: 10.1038/s41420-021-00427-x
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA ZFAS1 is a major regulator of epithelial-mesenchymal transition through miR-200/ZEB1/E-cadherin, vimentin signaling in colon adenocarcinoma

Abstract: Colon adenocarcinoma is a common cause of cancer-related deaths worldwide. Epithelial-mesenchymal transition is a major regulator of cancer metastasis, and increased understanding of this process is essential to improve patient outcomes. Long non-coding RNA (lncRNA) are important regulators of carcinogenesis. To identify lncRNAs associated with colon carcinogenesis, we performed an exploratory differential gene expression analysis comparing paired colon adenocarcinoma and normal colon epithelium using an RNA-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 37 publications
(33 reference statements)
0
29
0
Order By: Relevance
“…ZFAS1 is a major regulator of the epithelial–mesenchymal transition (EMT) through miR-200/ZEB1/E-cadherin and vimentin signaling in colon adenocarcinoma. 28 The expression level of AL031710.1 decreases with the increase in tumor stage of papillary renal cell carcinoma. 29 AL355102.4 is downregulated in clear cell renal cell carcinoma samples and indicates good prognosis when lowly expressed, which reveals that AL355102.4 is a risk factor with high gene expression.…”
Section: Discussionmentioning
confidence: 96%
“…ZFAS1 is a major regulator of the epithelial–mesenchymal transition (EMT) through miR-200/ZEB1/E-cadherin and vimentin signaling in colon adenocarcinoma. 28 The expression level of AL031710.1 decreases with the increase in tumor stage of papillary renal cell carcinoma. 29 AL355102.4 is downregulated in clear cell renal cell carcinoma samples and indicates good prognosis when lowly expressed, which reveals that AL355102.4 is a risk factor with high gene expression.…”
Section: Discussionmentioning
confidence: 96%
“…After searching through the publication, we have identified 9 lncRNAs that were suggested to sponge miR-200c in different types of cancer or in other diseases [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 30 ]. Among the identified lncRNAs, we have chosen those that could successfully detect specific products of less than 100 bp using TaqMan probe.…”
Section: Methodsmentioning
confidence: 99%
“…Among the identified lncRNAs, we have chosen those that could successfully detect specific products of less than 100 bp using TaqMan probe. For the purpose of expression analysis, we, therefore, selected the following lncRNAs: LUCAT1 , MALAT1 , lncTCF7 , XIST and ZFAS1 [ 20 , 21 , 22 , 27 , 28 ]. The other four lncRNAs, namely ATB , LINC02582 , N-BLR and ZEB1-AS1 [ 23 , 24 , 25 , 26 ], were excluded from further analysis due to the longer amplification product of pre-designed TaqMan probes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some lncRNAs are localized in the cytoplasm; they not only interfere with the post-translational modification of proteins and cause abnormal signal transduction but also affect the post-transcriptional expression of mRNAs in the cytoplasm through various mechanisms (e.g., by acting as ceRNAs) ( Chen, 2016 ). Imbalanced expression of some lncRNAs is frequently involved in the progression of numerous malignancies ( O’Brien et al, 2021 ; Wang Y. et al, 2021 ; Zhang et al, 2021 ). Recent studies have reported that lncRNAs are directly or indirectly involved in tumor immune regulation through a variety of mechanisms.…”
Section: Introductionmentioning
confidence: 99%